Online Shopping: Exploring the Cost and Convenience Benefits of Online Shopping (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The vast majority of online stores offer prices that are much lower than what you will find at a physical store. There are a few reasons for this. The first is because many people use the Internet to find cheaper items. Online business owners understand this. They will usually reduce their profit margin to get more customers. Another reason is because you can easily browse through dozens of different websites to find the best price. You can do the same at a mall, but it would take about an hour or longer. You also may not be taxed because most e commerce stores won't tax you unless they are stationed in your state.